Germany, Austria & Switzerland's best trips 33 amazing road trips - Williams, Nicola; SaChristiani, Kerry; Di Duca, Marc; Le Nevez, Catherine; Masters, Tom; O'Brein,Sally; Schulte-Peevers, Andrea; Ver Berkmoes, Ryan; SaWalker, Benedict (Footscray, Victoria, Australia Lonely Planet Publications Pty Limited, 2016)
Plan your trip. Welcome to Germany, Austria & Switzerland -- Classic trips -- Germany, Austria & Switzerland highlights -- If you like -- Need to know -- City guide -- Germany, Austria & Switzerland by region -- On the road. Northeastern Germany -- Northwestern Germany -- Southern Germany -- Austria -- Switzerland -- Road trip essentials.
At head of title: Lonely Planet.
Includes bibliographical references, discography, filmography and indexes.
Keywords: Automobile travel -- Guidebooks. -- Germany; Automobile travel -- Guidebooks. -- Austria; Automobile travel -- Guidebooks. -- Switzerland; Germany -- Guidebooks; Austria -- Guidebooks; Switzerland -- Guidebooks